Practice of trust towards leaders in the educational organizations. - Ling , Ying Leh; Abdullah, Abdul Ghani Kanesan (Universiti Sains Malaysia, 2014)
This study aims to identify the level of trust in the leaders and describes the psychometric properties of the instrument of trust against the leaders modified according to the situation and the uniqueness of the organization’s management system of education in Malaysia.